Priming With Toll-Like Receptor 3 Agonist Poly(I:C) Enhances Content of Innate Immune Defense Proteins but Not MicroRNAs in Human Mesenchymal Stem Cell-Derived Extracellular Vesicles - Pierce, Lisa M.; Kurata, Wendy E. (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) help fight infection by promoting direct bacterial killing or indirectly by modulating the acute phase response, thereby decreasing tissue injury. Recent evidence suggests that extracellular vesicles (EVs) released from MSCs retain antimicrobial characteristics that may be enhanced by pretreatment of parent MSCs with the toll-like receptor 3 (TLR3) agonist poly(I:C). Our aim was to determine whether poly(I:C) priming can modify EV content of miRNAs and/or proteins to gain insight into the molecular mechanisms of their enhanced antimicrobial function. Human bone marrow-derived MSCs were cultured with or without 1 µg/ml poly(I:C) for 1 h and then conditioned media was collected after 64 h of culture in EV-depleted media. Mass spectrometry and small RNA next-generation sequencing were performed to compare proteomic and miRNA profiles. Poly(I:C) priming resulted in 49 upregulated EV proteins, with 21 known to be important in host defense and innate immunity. In contrast, EV miRNA content was not significantly altered. Functional annotation clustering analysis revealed enrichment in biological processes and pathways including negative regulation of endopeptidase activity, acute phase, complement and coagulation cascades, innate immunity, immune response, and Staphylococcus aureus infection. Several antimicrobial peptides identified in EVs remained unaltered by poly(I:C) priming, including dermcidin, lactoferrin, lipocalin 1, lysozyme C, neutrophil defensin 1, S100A7 (psoriasin), S100A8/A9 (calprotectin), and histone H4. Although TLR3 activation of MSCs improves the proteomic profile of EVs, further investigation is needed to determine the relative importance of particular functional EV proteins and their activated signaling pathways following EV interaction with immune cells.